Growth factors and feeder cells promote differentiation of human embryonic stem cell into dopaminergic neurons: a novel role of fibroblast growth factor-20 - Correia, Ana Sofia; Anisimov, Sergey V.; Li, Jia-Yi; Brundin, Patrik (Frontiers in Neuroscience, 2008)
Human embryonic stem cells (hESCs) are a potential source of dopaminergic neurons for treatment of Parkinson’s disease (PD). Dopaminergic neurons can be derived from hESCs and display a characteristic midbrain phenotype. Once transplanted, they can induce partial behavioral recovery in animal models of PD. The potential research field faces several challenges that need to be overcome before clinical application of hESCs in a transplantation therapy in PD can be considered. These include low survival of the hESC-derived, grafted dopaminergic neurons after transplantation; unclear functional integration of the grafted neurons in the host brain; and, the risk of teratoma/tumor formation from the transplanted cells. This review is focused on our recent efforts to improve the survival of hESC-dervied dopaminergic neurons. We have examined the effect of fibroblast growth factor (FGF)-20 in the differentiation of hESCs into dopaminergic neurons. We supplemented cultures of hESCs with FGF-20 during differentiation on PA6 mouse stromal cells for three weeks. When we added FGF-20 the yield of neurons expressing tyrosine hydroxylase increased. We demonstrated that at least part of the effect is contributed by enhanced cell differentiation towards the dopaminergic phenotype as well as reduced cell death. We compare our results with those obtained in other published protocols using different sets of growth factors. Our data indicate that FGF-20 has potent effects to generate large number of dopaminergic neurons derived from hESCs, which may be useful for cell therapy in PD.